A dual‐limiting power balance controller for multiterminal VSC‐HVDC system. (5th February 2017) - Lu, Shuangyang; Lin, Weixing; Yao, Liangzhong; Wen, Jinyu; Li, Yan
Summary: To enable zero‐power tracking error in steady state and to ensure system security during power unbalance, we proposed a dual‐limiting power balance controller for multiterminal voltage‐source converter high‐voltage direct current (MTDC). The dual‐limiting controller is composed of an upper limiting loop and a lower limiting loop. By specifically setting the limits of the integrators and limits of the total output of the limiting loops, the dual‐limiting controller is automatically disabled if direct current terminal voltage stays within the specified limits and is automatically enabled if there is unbalanced power. Simulations on a 4‐terminal MTDC system under unbalanced power orders, alternating current faults, and wind power fluctuations verified the efficacy of the proposed controller. The dual‐limiting power balance controller is promising for direct current voltage control of MTDC.